Pemikiran Hamka Tentang Pandangan Hidup Muslim - Randika Firmansyah (UNISBA Press, 2022)
Abstract. Mass media can be used as a means to convey information to the public. The presence of mass media in the form of print media can be used as a means to change the way of view, opinion, even behavior that reads it. Therefore, print media is also used as a means of conveying da'wah messages to the community. One of the print media is the book, as the book studied in this, is